Caracterização e estudo da aplicabilidade do biossurfactante produzido por Bacillus subtilis LAMI005 a partir do suco de caju - Felix, Anne Kamilly Nogueira (2012)
The surfactants are amphipathic molecules which have in their chemical structure hydrophobic and hydrophilic segments, spatially separated to assist in the formation of emulsions available compounds and the microbial cell. Due to these characteristics, the emulsifiers decrease the surface tension at the interface of immiscible phases, allowing thus that they mix to form the emulsion. Many types of chemically synthesized surfactants are used used today, although the development of alternative products, less toxic and biodegradable, as so-called biosurfactants obtained by microbiological agents, is an important strategy in obtaining components more compatible with the environment and expanding specific properties and applications of these compounds. In this context, this study aims to characterize the biosurfactant produced by Bacillus subtilis LAMI005 using cashew apple juice as carbon source, to conduct studies of the structure and conformation of the compounds, thereby determining the functional groups belonging to the molecule, to study the toxicological effects of surfactin produced, designed to further understanding of the toxicity of the biosurfactant in vegetable and animal organisms; evaluate the maintenance of the characteristics of surfactants surfactin to be subjected to different environmental conditions, in addition to studying the stability of emulsions formed with biosurfactant which was produced in clarified cashew juice, adding value to the process, since the source used is available and inexpensive. The spectra obtained indicated the similarity between this work produced surfactin and surfactin standard (Sigma). The lipopeptide surface produced had a highly stable activity, with a CMC 12.5 mg.l-1 and capable of reducing the surface tension of water to 31.8 mN.m-1 and interfacial tension of n-hexadecane to 2 mN.m-1. The ability of emulsifying at high temperatures, acidic and basic pH and different concentrations of NaCl was also demonstrated. The phase diagrams shown the possibility of application of the biosurfactant in the bioremediation of waste treatment and cutting fluids. The biosurfactant also showed non-toxic when analyzed in the brine shrimp with LC50 equal to 612.27 μg.mL-1 forward and Lactuca sativa, presented at which germination index higher than 80% high concentrations, demostrating its potential for applications in the cosmetics industry , food and drugs. The biosurfactant produced also efficient in removing, approximately, 82% diesel and 77% petroleum adsorbed on sand.